Narasi Sufistik dalam Tafsir Mafātīḥ al-Ghaib: Analisis Penafsiran Sufistik Fakhr al-Dīn al-Rāzi dalam Tafsir Mafātīḥ al-Ghaib - Atfal, Khairul; Halimatussa’diyah, Halimatussa’diyah; Kusnadi, Kusnadi (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Tafsir Mafātīḥ al-Ghaib is a tafsir that criticizes Muktazilah from linguistic analysis. The period of al-Rāzi is known as the period of mixing tafsir with political interests, a particular school of thought or ideology. However, Abdul Mustaqim's writing does not mention the tendency of Sufism. Then, al-Alūsi's famous Sufi tafsir, in 'Ali Iyāzi's statement, is a form of replication of al-Rāzi's tafsir. Therefore, how can a tafsir that is considered Sufi in style be said to be a replica of the 'itiqādī style. Thus, this paper aims to find out how al-Rāzi responded when confronted with Sufism verses and reveal how Sufistic narratives, whether they will also depart from linguistic analysis or not, and how the depth of the narratives written by al-Rāzi. The research method used is a qualitative method using literature review. With descriptive-deductive analysis and referring to primary sources of al-Rāzi's works, it was concluded that not all Sufistic narratives were written in depth by al-Rāzi. He starts with the linguistic side and then draws the theological side. However, in al-Ra'd [13]: 28, he goes quite deep when dividing the meaning behind the word al-iṭmi'nān. This discovery can give a new perception that al-Rāzi's analysis is thick with linguistic analysis that is quite in-depth, although in the end it is drawn in a theological or Sufistic narrative.